172k views
1 vote
Enter the correct answer in the box. Use the sum of cubes identity to find the factors of the expression 8x^6 + 27y^3

User CoolMAn
by
5.2k points

2 Answers

5 votes
I need this answer too
User Tse
by
5.2k points
6 votes

Answer:

(2x^2 + 3y)(4x^4 - 6x^2y + 9y^2).

Explanation:

a^3 + b^3 = (a + b)(a^2 - ab + b^2) is the identity.

Comparing this with the sum in the question:

a = 2x^2 and b = 3y so we have:

8x^6 + 27y^3 = (2x^2 + 3y)(4x^4 - 2x^2*3y + 9y^2)

= (2x^2 + 3y)(4x^4 - 6x^2y + 9y^2).

User Aadhar Bhatt
by
5.3k points